Dielectric and electro-optical properties of zinc ferrite nanoparticles dispersed nematic liquid crystal 4'-Heptyl-4-biphenylcarbonnitrile. Issue 7 (27th May 2020) - Pandey, Fanindra Pati; Rastogi, Ayushi; Manohar, Rajiv; Dhar, Ravindra; Singh, Shri
ABSTRACT: In this work, comprehensive results on dielectric and electro-optical properties of pristine and zinc ferrite (ZnFe2 O4 ) nanoparticles (NPs) dispersed in host nematic 4ʹ-Heptyl-4-biphenylcarbonnitrile (7CB) systems are reported. The dielectric and EO properties of pristine and NPs dispersed (concentrations 0.05, 0.1, 0.15, 0.2, 0.3 and 0.5 wt%) into the host nematic system have been studied. We have seen uniform NPs dispersion into nematic 7CB up to 0.15 wt% concentration of NPs by the POM. The NPs aggregation starts at 0.2 wt% dispersion. It is shown that the dielectric and electro-optical properties are strongly influenced by the concentration of NPs in host nematic and applied electric field. The dielectric anisotropy is maximum for the NPs dispersed system of 0.15 wt% concentration. The Birefringence, parallel and perpendicular components of permittivity and conductivity are found to be dependent on temperature and concentration of NPs into host matrix. In pure nematic material, small memory is seen but in NPs dispersed systems noticeable memory is found. In particular, pronounced memory is found for the dispersed system of 0.3 wt% concentration of NPs. GRAPHICAL ABSTRACT: